Prospective randomized controlled trial comparing dynamic hip screw and screw fixation for undisplaced subcapital hip fractures. Issue 9 (24th September 2012) - Watson, Adam; Zhang, Yu; Beattie, Sally; Page, Richard S.
Abstract: Background: Neck of femur fractures (NOFFs) are a common cause of morbidity and mortality in our community. Minimally displaced intracapsular fractures are treated with internal fixation by a two‐hole dynamic hip screw (DHS) or three partially threaded cancellous screws. Data to support the superiority of one are limited. This prospective randomized controlled trial compares outcomes with these two fixation methods. Methods: We prospectively recruited patients over 50 years, with an acute fracture subcapital NOFF, who walked and lived independently, and were cognitively intact. They were randomized into DHS or cancellous screw groups and followed up for 2 years (overall 75.9%). Outcomes of mortality, revision, loss of fixation, avascular necrosis, surgical complications, WOMAC, Harris hip score and SF‐12 were measured. Results: We recruited 62 patients (31 DHS, 29 cancellous screws, 2 failed consent). Six deaths (19.3%) were seen in each group. A total of 3.2% of DHS (1 out of 31) and 10.3% (3 out of 29) of cancellous screw patients required re‐operation ( P = 0.272). There was no statistical significant difference in patient satisfaction, quality of life (QoL), radiological union or osteonecrosis. There are trends towards better functional scores and QoL in cancellous screws, particularly at 1 year ( P = 0.0061), but with a higher re‐operation rate. There was a combined mortality and transition to institutional care of 40.0% (24 out of 60) at 2 years. Conclusions: This study found no difference in outcomes between DHS and cancellous screws in the treatment of subcapital NOFFs in a fit, independent population, but we found a high level of physical decline in previously fit, independently ambulating patients. A large, multicentre trial will be required to differentiate between these two fixation methods.